EVALUATION OF THE IMPLEMENTATION OF SCIENCE LEARNING PROGRAM IN JUNIOR HIGH SCHOOLS, LAB SCHOOLS UNIVERRSITAS NEGERI JAKARTA - Desmiati Desmiati; Basuki Wibawa; Priono Priono (International Journal of Education, Information Technology, and Others, 2020)
The purpose of this study is to provide practical solutions to a problem, and determine further policies or decisions regarding the implementation of a science learning program by utilizing learning resources in SMP Lab School UNJ. The average value of students has met the minimum competency and satisfactory for students, the average value of students' natural sciences per year always increases, this is inseparable from the way of teaching an interesting teacher and detailed explanation is equipped with a summary of notes of each subject matter and also support infrastructure learning resources that are quite complete and adequate both in the Laboratory and in the Library so that it really helps children to understand and understand the lesson. The completeness of the learning resource infrastructure in the school really helps students in achieving good grades, this is in line with theories of learning resources, and this is also proven at the 2018 UNBK for the IPA score of Jakarta's Labschool Middle School, ranked 5th (Fifth) in DKI Jakarta with an average UN score of 81.92, for 2019 the best natural sciences of Labschool Middle School number One in East Jakarta for the average value is 92.53 and for the second best private SMP in DKI Jakarta with an average value of an average of 9,253.